ANCIENT CARAVAN ROUTES WITH THE HELP OF PLACE NAMES ABOUT DETECTION CAPABILITIES (using the example of Jizzakh region) - Khakimov, K.M.; Usmanov, M.R.; Abdiramanov, J.B. (SCIENCE and SOCIETY, 2026)
The article analyzes toponyms associated with ancient caravan routes and reflecting historical events of that period using specific examples from the Jizzakh region. Due to the fact that the territory of present-day Uzbekistan is located at the crossroads of the “Great Silk Road”, toponyms associated with caravan routes occupy a special place in the toponymy of the region. In this sense, the object of study of this article, the toponymy of the Jizzakh region, is no exception. In addition, with the help of geographical names that appeared on ancient caravan routes, it is possible to identify not only the route of caravans that had a positive impact on the development of the region at the time, but also to obtain valuable information about the language, customs, national values and ethnocultural characteristics of the peoples living or who lived in this territory. It is therefore important to study toponyms associated with ancient caravan routes and determine their scientific etymology through toponymic research.
Keywords: toponymy; geographical names; etymology; caravan routes; territoriality; historical layers; national values